Resist Covid-19: Innovation, intellectual property, and public education. A look from the perspective of four film clubs in the city of Barranquilla (2022)
The purpose of this article is to explore the dynamics of the film clubs of the city of Barranquilla under the lens of innovation and intellectual property awareness in the framework of the Covid 19 pandemic. It`s a response to the lack of literature on film clubs in Barranquilla and the Colombian Caribbean despites the significant number of private initiatives that operate in this City and that have the interest of bringing together and to educate an audience with and about film and the audiovisual world. The present study attempts to provide an answer to how the Pandemic affected these public training spaces and how they have innovated, and incorporated a wider understanding of copyrights, intellectual property, royalties, among other aspects to continue operating in the midst of this contingency. To identify the subjects of potential interest for our research, we used a snowball sampling strategy to gather the sample of four film Clubs in Barranquilla, whose members, and organizers were interviewed. It was essential to know the demographics of film club members and organizers and the circumstances under which they joined. Likewise, how the film club works, the operating time, audience, and origin, to have a reference point with which we can compare in the future and how organizers and their spaces found a way to adapt to quarantine and the mandatory isolation amid covid-19 Pandemic. Finally, this research helped us to conclude that the Covid-19 pandemic has been a crucial factor in incorporating innovations in the formation processes of audiences related to cinema and audiovisuals, and with this, making the transition to the use and appropriation of new technologies and practices in the city's film clubs with the tendency to maintain, beyond the pandemic, some of the changes applied, including blended approaches to this public's training method. Further investigation is necessary on these issues considering the process of creating and sustaining spaces and opportunities for the promotion of cultural diversity and the formation of audiences as proposed by the Colombian state through its public policies.